Bacterial diversity determination using culture-dependent and culture-independent methods - M. Ghiasian; A. Akhavan Sepahy; M.A. Amoozegar; S. Saadatmand; M. Shavandi (Global Journal of Environmental Science and Management)
Mud volcanoes are taken into consideration by geologists and oil industry experts have given their association with oil and gas reserves and methane greenhouse gas production in hydrosphere and atmosphere. Gomishan mud volcano phenomenon in the southeastern edge of the Caspian Sea, given its oil and gas resources, has been studied by some geologists in terms of geology and tectonics but not in terms of microbiology. Accordingly, it seems necessary to study this phenomenon from the perspective of microbiology in order to identify prokaryotes living in this area. Prokaryotes diversity in Mud volcano has been studied by cultivation techniques, fluorescence in situ hybridization, and denaturing gradient gel electrophoresis of PCR-amplified fragments of 16S rRNA genes. Total cell abundance in the mud volcano from 1×101-6×101per milliliter was determined by 4', 6-diamidino-2-phenylindole direct count. The detectable proportion of Archaea to Bacteria in the community by FISH was one to five. High viable counts (1 – 3 × 106) were obtained in culture media. A total of 122 isolates were obtained, 46 colonies were selected based on primarily morphological and physiological traits, and their 16S rRNA sequences were determined. The isolated genera included Halomonas (20%), Arthrobacter (5%), Kocuria (5%), Thalassobacillus (5%), Marinobacter (20%), Paracoccus (5%), Roseovarius (5%), Jeotgalicoccus (5%), Bacillus (15%), and Staphylococcus (15%). Regarding DGGE analysis, selected bands were obtained from the gels, reamplified and sequenced. Overall, 75% of the bacterial sequences were related to Rahnella and 25% related to Serratia.